Is there an association between out-of-pocket hospital costs, quality and care outcomes? A systematic review of contemporary evidence - Ramya Walsan; Rebecca J. Mitchell; Jeffrey Braithwaite; Johanna Westbrook; Peter Hibbert; Virginia Mumford; Reema Harrison (BMC, 2023)
Abstract Background Out of pocket (OOP) costs vary substantially by health condition, procedure, provider, and service location. Evidence of whether this variation is associated with indicators of healthcare quality and/or health outcomes is lacking. Methods The current review aimed to explore whether higher OOP costs translate into better healthcare quality and outcomes for patients in inpatient settings. The review also aimed to identify the population and contextual-level determinants of inpatient out-of-pocket costs. A systematic electronic search of five databases: Scopus, Medline, Psych Info, CINAHL and Embase was conducted between January 2000 to October 2022. Study procedures and reporting complied with PRISMA guidelines. The protocol is available at PROSPERO (CRD42022320763). Findings A total of nine studies were included in the final review. A variety of quality and health outcomes were examined in the included studies across a range of patient groups and specialities. The scant evidence available and substantial heterogeneity created challenges in establishing the nature of association between OOP costs and healthcare quality and outcomes. Nonetheless, the most consistent finding was no significant association between OOP cost and inpatient quality of care and outcomes. Interpretation The review findings overall suggest no beneficial effect of higher OOP costs on inpatient quality of care and health outcomes. Further work is needed to elucidate the determinants of OOP hospital costs. Funding This study was funded by Medibank Better Health Foundation.